Rational Design of ICT-Based Fluorescent Probe with AIE and NIR Properties for Hypochlorite Determination. Issue 1 (1st January 2022) - Xu, Chenggong; Wu, Tian; Duan, Lizheng; Zhou, Yunhao; Zhou, Yanmei
Abstract : In recent years, the easily synthesized fluorescent probes with good photophysical and sensing properties have attracted widespread attention. Herein, by utilizing the fluorescence regulation effect of electron push-pull effect and the oxidation property of hypochlorite (ClO − ) to C=N double bonds, we rationally proposed two intramolecular charge transfer (ICT)-based fluorescent probes with typical aggregation-induced emission (AIE) properties for ClO − detection. The synthesis process of the two probes is very convenient, and both of them can exhibit significant colorimetric and fluorescence changes within 3 min in the presence of ClO − . Moreover, compared with Probe A, the Probe B with near-infrared (NIR) fluorescence centered at 677 nm was successfully applied to ClO − determination in tap water and food samples as well as live cell imaging.